The Festivity in Honour of Our Lady of Antime in Fafe: An Emerging Tourist Resource? - José Luis Braga; Catarina Mota; Sandra Brás; Isabel Borges (Religions)
The aim of this study was to analyse the motivations of the participants of the festivity in honour of Our Lady of Antime in Fafe (located in the north of Portugal) and provide an overview of the tourism opportunities and impacts associated with the event. To this end, the study analysed the main events on the programme for the 2024 edition of this religious festivity. According to the interviews and participant observations, the impact of the religious festivity in honour of Our Lady of Antime on the faithful who participated was evident. For this study, semi-structured face-to-face interviews and participant observations were conducted, and the former were recorded for subsequent content analysis and categorisation. Participant observation was conducted, focusing on the events that occurred during the religious festivity in honour of the Lady of Antime. The limitations of this study relate to the fact that this is a resource that has not yet been explored as a lever for religious tourism in the municipality, although it has received more media attention in recent years. After carrying out this study, it was possible to conclude that the religious festivity in honour of Our Lady of Antime is attracting more and more believers, and that this event has become a resource that is complementary to the basic tourist resources of the destination of Fafe.